PENERAPAN FLOW-BASED CHATBOT MENGENAI SKPM DI LINGKUNGAN UPN “VETERAN” JAWA TIMUR - Faiz Daniar, Ivan; Anjani Arifiyant, Amalia; Saka Fitri, Anindo (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The purpose of this study is to develop a WhatsApp-based Chatbot system that can answer questions related to SKPM, utilizing a platform that is familiar to many students. The methodology used in developing this system is waterfall, which consists of the stages of Communication, Planning, Modeling, Construction, and Deployment. Starting with interviews and observations around SKPM. Then identifying the needs of the Chatbot system to be created, then creating a design for the Architecture, Flowchart, Usecase, Activity, Sequence and Interface of the Chatbot system. System testing is carried out using the Blackbox testing method, while the measurement of system usability uses the Chatbot Usability Questionnaire (CUQ). The results of the CUQ test show that the Chatbot system successfully manages various interaction scenarios with users well, with a CUQ score of 74%. This finding confirms that the application of Chatbot as a means of communication in an academic context can increase efficiency and accelerate the dissemination of relevant information to students.